REGULATION OF ENTERPRENEURSHIP IN AZERBAIJAN AND ANALYSIS OF ITS CURRENT SITUATION - HASANOV, Umid Fazil oglu (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It is noted here that in our country, “entrepreneurial activity” means an activity carried out independently by a person whose main goal is  to make a profit from the use of property, the provision of goods, the performance of works or the provision of services.During the research, many methods were used, including analysis, observation, comparison, statistics, systematization and generalization.To determine the role of small and medium entrepreneurship in the development of economy in Azerbaijan by conducting comprehensive research based on world experience and to show the steps to be taken in this direction.It can provide a useful database and the right direction for Small and Medium Enterprises operating in Azerbaijan and its regions. The results of the research can contribute to the efficient operation of Small and Medium Enterprises in Azerbaijan. At the same time, it can be used as a source in the teaching of subjects within the framework of research in universities.In conclusion, let’s note that the Republic of Azerbaijan’s active commitment to the development of entrepreneurship is demonstrated by hosting and organizing important entrepreneurship forums every year. These initiatives underline the country’s strategic approach to ensuring socio-economic development, particularly by promoting entrepreneurial spirit among the youth. The government of Azerbaijan is active in promoting entrepreneurship, cooperating with various institutions and supporting entrepreneurs.The II Forum of Young Entrepreneurs, held in Baku in 2021, emphasized the commitment of youth to entrepreneurship in Azerbaijan and the promotion of dialogue between entrepreneurs, government representatives and representatives from both the public and private sectors. Led by multiple stakeholders, the event provided a platform to share success stories and discuss available entrepreneurial support.
Keywords: Azerbaijan; entrepreneurship; regulation; current situation; analysis